Effect of acute fatigue on force generation accuracy and repeatability in youth athletes - Agnieszka D. Jastrzębska (Scientific Reports)
Abstract The study aimed to evaluate the acute effect of the incremental running test on the accuracy and repeatability of submaximal force generation in adolescent athletes (biathletes and runners) with different training regimes. The isometric force generation was assessed in biathletes and runners by examining left and right elbow extension (LEE; REE); flexion (LEF; REF); left and right knee extensions (LKE; RKE) before and after the test. The mean force of 10 sub-maximal targeted force pulses (F mean ) and force variability parameters: standard deviation and coefficient variation were used for accuracy and repeatability estimation. Biathletes generated forces more accurate and exhibit better repeatability of produced forces than runners. Mean force measured in fatigue conditions, for both groups, did not vary significantly from rest measurements. Before testing biathletes exhibited significantly lower REE and LEE, and after testing lower REF and LEF variability than runners. After testing there was a significant drop of variability in elbows flexion but not extension and RKE in biathletes. Insignificant downward trend of variability parameters were found in runners. The presented findings corroborate sport-specific force generation ability alteration in response to exhaustive effort. Tracking force generation over time may be useful in the monitoring of training loads and specific training adaptations.